(untitled) (Pragya Darshan प्रज्ञा दर्शन, 2025)
Investors commonly perform investment analysis by making use of fundamental analysis, technical analysis, and judgment. The main purpose of the study was to examine the relationship between independent variables (accounting information, firm image, and advocate recommendations) and investment decisions. The study adopted descriptive and explanatory research design to deal with issues. Nepalese investors in the Stock Market are taken as the population of the study. 80 respondents were selected based on the snowball sampling technique. This study is based on primary data. The study collected the required data through a structured questionnaire The questionnaire was developed consisting of Yes-No questions, ranking questions, and Likert scale questions were asked on the questionnaire. Cross tab, mean, standard deviation variance, and correlation are applied to analyze the collected data using SPSS Software. According to the ranking question results, accounting information is the most important factor influencing investment decisions, followed by a firm’s image and advocate recommendations as the least important. The descriptive results also show that accounting information is the top influence, followed by the firm’s image, and advocating recommendations. Accounting information, advocate recommendations, and a firm’s image have a positive relationship with investment decisions. Financial advisors and firms must provide accurate & sufficient information for a better business environment. Investors need to analyze market dynamics properly using various tools before investing. Future researchers can study investment decisions by taking another variable in another geography with a large sample size.